Etched Silicon Planar CRL Optics for the High-Energy X-ray Diffraction Beamlines 11-ID-B and 11-ID-C at the APS. Issue 1 (1st December 2022) - Ruett, Uta; Gades, Lisa; Borkiewicz, Olaf; Quaranta, Orlando; Beyer, Kevin; Jennings, Guy; Suzanne Miller, C.; Miceli, Antonino
Abstract: The focusing of high-energy X-rays is most commonly achieved by commercially available compound refractive lenses (CRL), which are added together in larger structures. There is a need for high-energy X-ray beamlines to enable focusing in only one dimension down to a few micrometers to study layered materials and thin films. High-energy X-rays above 50 keV require often 100 lenses or more, therefore it is more efficient to etch the complete arrays of lenses into a monolithic substrate like a silicon wafer. Custom lens arrays were fabricated for the high-energy x-ray beamlines 11-ID-B, and 11-ID-C at the Argonne National Laboratory. The fabrication required tuning parameters of the Bosch process to optimize the etching of deep vertical sidewalls at a reasonable speed without overheating. The beamline 11-ID-B is equipped with lens arrays of 85-110 lenses for 59 keV and 190-250 lenses for 87 keV photon energy, focusing the beam vertically below 5.0 µm at the sample positions between 1600 mm to 2100 mm. 11-ID-C has received arrays of 435 lenses that focus 106 keV X-rays to a vertical height of 2.0 µm at the sample position. In both cases, the flux density gain in the focal spot is larger than a factor of 20, relative to using slits to cut the beam size. The lens setup is permanently installed and can be moved in and out of the beam during the experiment without further alignment. The lenses have enabled operando diffraction studies on interfaces in batteries and the development of pair distribution function (PDF) analysis using grazing incidence geometry.